A Composite Matching Layer with Anti-Reflection Characteristics for Broadband Acoustic Scattering Reduction. (15th December 2021) - Li, Shande; Wu, Xiaoxun; Duan, Jinxiu; Yuan, Shuai; Wang, Cun; Ma, Yane; Zhang, Zhifu
Abstract : A composite matching layer composed of periodically arranged scatters with anti-reflection (AR) characteristics is proposed for broadband scattering reduction. The anti-reflection structure is composed of periodically arranged metal foam scatters, and it is the first attempt to be applied in the field of suppressing acoustic reflection. A complete theoretical model is developed to reveal the mechanism of scattering reduction and acoustic absorption based on effective medium theory and the transfer matrix method. The correctness and effectiveness of the theoretical model are verified by the finite element method (FEM), showing acoustic reflectance of less than 13.5% at broadband frequencies. The variation trends of reflectance are deeply investigated. The superior acoustic scattering reduction performance suggests that the matching layer possesses potential for acoustic imaging equipment and acoustic stealth.